2010
DOI: 10.1016/j.exger.2010.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in PTEN and increase in Akt expression and neuron size in aged rat spinal cord

Abstract: PTEN is a tumor suppressor gene known to play an important role in the regulation of cell size. In this study we compared PTEN expression in the spinal cord of young (5 mo.) versus aged (32 mo.) female rats and correlated them with alterations in neuron size and morphology in the same animals. Total and phosphorylated PTEN (pPTEN) as well as its downstream target phosphorylated Akt (pAkt) were assessed by western blotting. Spinal cord neurons were morphometrically characterized. Total PTEN, pPTEN and total Akt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…With aging, there is thought to be a decline in motor unit number, but a compensatory increase in collateral axonal and terminal sprouting, resulting in an increase in motor unit size (Deschenes, et al, 2010;McNeil, et al, 2005;Vandervoort, 2002). Studies of lower motor neurons in aging humans and rodents have identified alterations to the cell soma size (Miyata, et al, 2008;Rodrigues de Amorim, et al, 2010), degeneration of dendritic and axonal integrity or number (Miyata, et al, 2008), alterations in protein expression (Finazzo, 1994;Hideyama, et al, 2012;Portiansky, et al, 2006;Rodrigues de Amorim, et al, 2010;Rygiel, et al, 2014;Vogelsberg, et al, 1997;Xie, et al, 2000), as well as changes in electrochemical properties and motor neuron firing rates (Christie and Kamen, 2006;Kalmar, et al, 2009;Kamen, et al, 1995;Kido, et al, 2004;Tracy, et al, 2005). However, the literature is not consistent regarding the effects of age on motor neuron number with some studies reporting no change (Chai, et al, 2011;Chopek and Gardiner, 2010), and others indicating substantial loss (Hashizume, et al, 1988;Ishihara, et al, 1987;Jacob, 1998;Kanda, 2002;Lexell, 1997;Tomlinson and Irving, 1977;Xie, et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…With aging, there is thought to be a decline in motor unit number, but a compensatory increase in collateral axonal and terminal sprouting, resulting in an increase in motor unit size (Deschenes, et al, 2010;McNeil, et al, 2005;Vandervoort, 2002). Studies of lower motor neurons in aging humans and rodents have identified alterations to the cell soma size (Miyata, et al, 2008;Rodrigues de Amorim, et al, 2010), degeneration of dendritic and axonal integrity or number (Miyata, et al, 2008), alterations in protein expression (Finazzo, 1994;Hideyama, et al, 2012;Portiansky, et al, 2006;Rodrigues de Amorim, et al, 2010;Rygiel, et al, 2014;Vogelsberg, et al, 1997;Xie, et al, 2000), as well as changes in electrochemical properties and motor neuron firing rates (Christie and Kamen, 2006;Kalmar, et al, 2009;Kamen, et al, 1995;Kido, et al, 2004;Tracy, et al, 2005). However, the literature is not consistent regarding the effects of age on motor neuron number with some studies reporting no change (Chai, et al, 2011;Chopek and Gardiner, 2010), and others indicating substantial loss (Hashizume, et al, 1988;Ishihara, et al, 1987;Jacob, 1998;Kanda, 2002;Lexell, 1997;Tomlinson and Irving, 1977;Xie, et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Our data also suggest that cytoplasmatic accumulation of lipofuscin pigments in aged neurons [7] while apparently devoid of toxic effects, may contribute to increasing cell size. As mentioned above, the expression of PTEN, a tumor suppressor gene known to play an important role in the regulation of cell size, has been shown to decrease in the spinal cord of aging rats [10] . This decrease may play a role in the age-related increase in neuronal size reported here.…”
Section: Discussionmentioning
confidence: 92%
“…In fact, there is scarce information even on the general morphological changes in the spinal cord of aging rats. In previous studies we have observed that there is an increase in the number of neurofilaments present in the gray matter of aged rats [7] , changes in the lectinhistochemical pattern [8] , a complete loss of neuron-specific nuclear protein (NeuN) immunoreactivity in cervical, thoracic and lumbar segments of aged female rats [9] , as well as a decrease in the expression of a phosphatase and tensin homologue on chromosome 10 (PTEN), a tumor suppressor gene known to play an important role in the regulation of cell size [10] .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, aging in the normal brain and spinal cord has been associated with moderate degrees of neurochemical changes, structural derangement and neuronal damage [13][14][15][16]. There are some reports about age-related changes of aII-spectrin proteolysis in the hippocampus [17,18] and in some motor neurons which show apoptosis in the aged rat lumbar enlargement through a caspase-dependent manner [19].…”
Section: Introductionmentioning
confidence: 97%